EL IMPACTO SOCIAL DE LOS PROYECTOS DE AGUA Y ALCANTARILLADO EN LOS SECTORES POPULARES DE LIMA METROPOLINA 2008 - Meneses Rivas, Max (2010)
This study aims to assess the social impact of sewage system and water projects on low-income sectors of Lima City in 2008. First, the problem of water and sewage system that affect more than one million people in Lima City is exposed. Then the social actors who take part in water and sewage system project execution are identified and finally the social impacts of the projects in the urban popular sectors are stated.